Measurement of Cardiovascular Disease Risk from Air Pollution in Jakarta: A Longitudinal Study of the Population Aged 40–60 Years - Ayu Novitrie; Esa Zahirah; M. Ramadhani Firmansyah; M. Nazhim Alhani; Lisa Rizky Amalia (Knowledge and Environmental Science for Living and Global Health, 2025)
Fine particulate matter (PM₂.₅) air pollution has long been identified as a crucial contributor to cardiovascular diseases in big cities with high air emissions like Jakarta. Long-term exposure to PM₂.₅ can trigger systemic inflammation, endothelial dysfunction, and accelerated atherosclerosis, thereby potentially increasing the incidence of major adverse cardiovascular events (MACE). This research aims to identify the risk of cardiovascular disease (CVD) from long-term exposure to PM₂.₅ among those aged 40–60 years and verify the hypothesis that higher concentrations of PM₂.₅ are related to higher incidences of MACE and values of CVD biomarkers. This longitudinal study involved 2,000 respondents aged 40–60 with more than three years of residence in Jakarta, selected via multistage sampling. PM₂.₅ exposure was estimated annually according to residence location. Analysis used Cox proportional hazards models to assess MACE risk and linear mixed-effects models for biomarker changes. Results showed exposure variation between tertiles (12–42 µg/m³) with a strong dose–response pattern; the highest exposure group had four times higher incidence of MACE than the lowest tertile. Exposure was also linked to increased blood pressure, LDL, hs-CRP, HbA1c, and accelerated CIMT thickening. These findings have significant implications for air quality management policies to minimize cardiovascular risk in sensitive age groups. Overall, this study highlights the urgent need to reduce PM₂.₅ concentrations as a preventive measure against CVD in densely populated metropolitan areas.